Off-Grid Solar System Monitoring Based on ESP-32 and INA219 in Pesanggrahan Gordomulyo - zufar permana Muqorrobin; Akhmad Nawawi; Achmad Aris Ardani; Singgang Putra Setia; Reza Rahmadian (Universitas Negeri Surabaya or The State University of Surabaya, 2024)
The main problem in the highland area of Pesanggarahan Gordo Mulyo is the difficulty of monitoring and maintaining PLTS due to the remote location and no reliable communication signal. As a solution, this research developed a remote PLTS monitoring system using ESP32 and Handy Talkie communication, which allows automatic data transmission without internet connection. This research contributes to the optimization of the monitoring system adapted to the surrounding environmental conditions. Testing has 3 categories, in the PV solar panel monitoring test, the highest voltage is 37.1 V, the highest current is 2.1 A, and the maximum power generated is 81 W. Error calculations are also carried out to see the performance of the INA219 sensor with a multimeter measuring instrument, the test results for voltage, current, and power are 0.3%, 1.8%, and 1.26%. The last test is sending data in the form of voice through HT transmission, the data sent is similar to the data received in five tests. Based on each test, this tool has a small error rate, so it can be one of the innovations in the world of monitoring solar power plants.